Revisiting fosfomycin to treat urinary tract infections in the era of rising carbapenem resistance - Kumari, Sweety; Chattopadhya, Debasish; Upadhyay, Shalini; Bharara, Tanisha; Khandait, Manisha; Dubey, Anshika (Asian Journal of Medical Sciences, 2025)
Background: Most of the studies on antibiotic resistance are pre-judiced over the use of last-resort antibiotics for Multidrug resistant organisms (MDRO) and fail to acknowledge the effectiveness of older antibiotics. There is a dearth of information regarding the susceptibility of fosfomycin and nitrofurantoin, which are oral alternatives for such infections. Aims and Objectives: To study the antibiotic susceptibility profile of uropathogenic Escherichia coli and infer whether fosfomycin can be used as an efficient oral option for the management of uncomplicated urinary tract infection (UTI), especially in carbapenem-resistant cases. Materials and Methods: Clean catch midstream urine samples from cases clinically suspected of UTI received for culture were processed using standard guidelines for microbiological procedures. Antimicrobial sensitivity was performed through the Kirby Bauer disc diffusion method. Discrepant results were confirmed with VITEK 2. Results: This study reports antimicrobial susceptibility pattern of 100 E. coli isolated from urine samples of patients with signs and symptoms suggestive of UTI. There was a female predominance in the study population and the most affected age group was 20–40 years (52%). Most specimens were received from the obstetrics and gynecology department (32%) followed by General medicine (28%). Higher sensitivity was observed for fosfomycin (97%), amikacin (80%), and meropenem (79%). Conclusion: Fosfomycin is an oral, safe, and efficient antibiotic for UTI. It is a valuable alternative for outpatient treatment of MDROs causing UTI. Thus, decreasing hospitalization and consequently reducing the financial burden of treatment for the patients.